PENGARUH TRIPUSAT PENDIDIKAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Muhammad Daliani (JURNAL CURERE, 2019)
The environment is very influential on the pattern of thinking and routine activities of students, moreover the desire for student learning interest which inevitably affects student learning outcomes. Many students whose activities only play with their friends, they do not want to learn because other friends also do not study. This study aims to determine the effect of the educational environment both family, school and community environment on student learning outcomes. The subjects of this study were SMK Ar-Rahman students with Randome Sampling 200 students from 24 classes with a total population of 750 students. Data collection techniques in this study used questionnaires, observation and documentation.The data analysis technique is done by calculating the "product moment correlation". The results of the correlation between tripusat education (family environment, school environment and community environment) with students' mathematics learning outcomes showed a significant relationship. This is shown from the results of the correlation obtained from the family environment of 0.487, the school environment of 0.576 while the community environment is 0.289 with a significant level < 0.05 so the hypothesis is accepted. Sehinggan it can be concluded that the environment that has a strong relationship with students' mathematics learning outcomes is the school environment while the weak relationship that influences student learning outcomes is the community environment.